Modernizing Non-Profit Law in Canada - Singer, Samuel (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2023)
Non-profit corporations benefit from significant tax subsidies, but they are largely regulated by corporate statutes rather than tax law. Recent legislative reforms in Canada have sought to modernize non-profit statutes to reflect the changing non-profit sector, with a focus on increasing accountability and fairness. Yet, despite the increasingly national reach of non-profits, governance and financial transparency requirements can differ considerably between jurisdictions. This article compares non-profit rules about directors and financial review in Alberta, British Columbia, Ontario, and federally. It demonstrates how modern non-profit law reforms make regulatory choices about governance and financial transparency requirements based on local policy priorities. The article then uses tax expenditure analysis to argue for a national perspective that considers the different regulatory burdens facing non-profits receiving the same federal tax subsidies. It finds that inconsistent rules between jurisdictions raise significant accountability and fairness concerns. For smaller non-profits, uninformed incorporation choices may result in a higher compliance burden. For non-profits seeking a lighter regulatory load, the uneven regulatory landscape may lead to jurisdiction shopping. The article argues that the increased harmonization of non-profit law across Canada is key to continuing the work of modernizing non-profit law. It concludes by identifying potential law reforms and their limitations.